ElewsMart: company analysis of Elews Mart / Ahmad Amin Ahmad Azizan ... [et al.] - Ahmad Azizan, Ahmad Amin; James, Alan; Mohd Ali, Alia Nadirah; Samsul Buhari, Muhammad Syafiq Izzuddin; Osman, Nur Nadhia Natasya (2021)
The main purpose of this case study is to analyze the small business that our group members have chosen, which ElewsMart is. ElewsMart is a retail company that sells a variety of products with a low price and high quality products. ElewsMart is a physical retail shop that owned by a popular preacher called Ustaz Ebit Lew. ElewsMart uses online platforms such as Facebook, Instagram, and Twitter to promote this shop. One of the main findings that is crucial in this case study is SWOT analysis of the business. In this study, we will look for the internal and external causes or factors that can influence the business. In terms of the SWOT analysis, we can identify the advantages for the business, weaknesses of the company, threats and anything related to the business.